Transcription factor Ap2b regulates the mouse autosomal recessive polycystic kidney disease genes, Pkhd1 and Cys1 - Maoqing Wu; Naoe Harafuji; Amber K. O’Connor; Ljubica Caldovic; Ljubica Caldovic; Lisa M. Guay-Woodford; Lisa M. Guay-Woodford (Frontiers in Molecular Biosciences, 2023)
Transcription factor Ap2b (TFAP2B), an AP-2 family transcription factor, binds to the palindromic consensus DNA sequence, 5′-GCCN3-5GGC-3’. Mice lacking functional Tfap2b gene die in the perinatal or neonatal period with cystic dilatation of the kidney distal tubules and collecting ducts, a phenotype resembling autosomal recessive polycystic kidney disease (ARPKD). Human ARPKD is caused by mutations in PKHD1, DZIP1L, and CYS1, which are conserved in mammals. In this study, we examined the potential role of TFAP2B as a common regulator of Pkhd1 and Cys1. We determined the transcription start site (TSS) of Cys1 using 5′ Rapid Amplification of cDNA Ends (5′RACE); the TSS of Pkhd1 has been previously established. Bioinformatic approaches identified cis-regulatory elements, including two TFAP2B consensus binding sites, in the upstream regulatory regions of both Pkhd1 and Cys1. Based on reporter gene assays performed in mouse renal collecting duct cells (mIMCD-3), TFAP2B activated the Pkhd1 and Cys1 promoters and electromobility shift assay (EMSA) confirmed TFAP2B binding to the in silico identified sites. These results suggest that Tfap2b participates in a renal epithelial cell gene regulatory network that includes Pkhd1 and Cys1. Disruption of this network impairs renal tubular differentiation, causing ductal dilatation that is the hallmark of recessive PKD.